2021
DOI: 10.3389/fnhum.2021.679977
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-Dependent Changes in Quantified Resting Cerebral Perfusion With Multiple Sessions of Transcranial DC Stimulation

Abstract: Transcranial direct current stimulation (tDCS) to the left prefrontal cortex has been shown to produce broad behavioral effects including enhanced learning and vigilance. Still, the neural mechanisms underlying such effects are not fully understood. Furthermore, the neural underpinnings of repeated stimulation remain understudied. In this work, we evaluated the effects of the repetition and intensity of tDCS on cerebral perfusion [cerebral blood flow (CBF)]. A cohort of 47 subjects was randomly assigned to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…However, a high interindividual variability exists ( 112 ). Additionally, it has again been demonstrated that repetitive sessions have cumulative effects ( 113 , 114 ).…”
Section: Non-invasive Brain Stimulation As a Therapeutic Option For F...mentioning
confidence: 97%
See 1 more Smart Citation
“…However, a high interindividual variability exists ( 112 ). Additionally, it has again been demonstrated that repetitive sessions have cumulative effects ( 113 , 114 ).…”
Section: Non-invasive Brain Stimulation As a Therapeutic Option For F...mentioning
confidence: 97%
“…TDCS-effects on CBF have been demonstrated to be dose-and polarity-dependent (111, 112). Hence, anodal tDCS increased CBF with higher increases at greater intensities (111,113,114), whereas cathodal tDCS decreased CBF (111, 112). However, a high interindividual variability exists (112).…”
Section: Non-invasive Brain Stimulation (Nibs) Techniques For the Tre...mentioning
confidence: 99%
“…Finally, the aftereffects of the electric field may continue to exist for several minutes or even hours after stimulation. The plasticity of synaptic connections may be reformed and enhanced [ 60 ], and repeated stimulation may produce cumulative effects [ 61 ].…”
Section: Discussionmentioning
confidence: 99%